Bone mineral density in young sprinters and young active men - El Hawly, W.; Zunquin, G.; Pinti, A.; El Hage, Z.; Bassim, Y.; El Hage, R. (Science & Sports, 2024)
Introduction The main aim of this study was to compare bone health parameters in young active sprinters and young active men.